2015
DOI: 10.1038/boneres.2015.26
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo 3D osteocyte network construction with primary murine bone cells

Abstract: Osteocytes reside as three-dimensionally (3D) networked cells in the lacunocanalicular structure of bones and regulate bone and mineral homeostasis. Despite of their important regulatory roles, in vitro studies of osteocytes have been challenging because: (1) current cell lines do not sufficiently represent the phenotypic features of mature osteocytes and (2) primary cells rapidly differentiate to osteoblasts upon isolation. In this study, we used a 3D perfusion culture approach to: (1) construct the 3D cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
4
41
0
Order By: Relevance
“…In comparison to our previous results on murine long bone samples,[32] it took a less number of digestion cycles to isolate cells from human bone fragments. Also, the number of isolated cells became significantly less after the eighth digestion cycle (i.e., “D8”) for the human samples.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…In comparison to our previous results on murine long bone samples,[32] it took a less number of digestion cycles to isolate cells from human bone fragments. Also, the number of isolated cells became significantly less after the eighth digestion cycle (i.e., “D8”) for the human samples.…”
Section: Resultsmentioning
confidence: 71%
“…1, we previously reported[32] that the physiological morphology and biological functions of murine primary osteocytes can be replicated ex vivo by their 3D network construction in microfluidic culture chambers. We used a microbeads-guided assembly approach that: (1) consists of 3D cellular network of primary osteocytes, and (2) mitigate the rapid osteoblastic dedifferentiation and proliferation of primary osteoblast-like encountered in conventional 2D culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, our results suggested that the osteocyte phenotype of the harvested cells could be preferentially preserved inside of the tissue structure due the 3D confinement effect of microbeads as mentioned earlier. As it is beyond the scope of this device-centric paper, we report elsewhere 30 in details that these reconstructed osteocytes express SOST gene which produces sclerostin, as determined by both PCR and histological immunostaining. In contrast, this key osteocytic gene expression is lost within a few weeks of conventional 2D culture, as the osteocytes differentiate to osteoblasts.…”
Section: Reconstruction Of 3d Cellular Network With Primary Murine Osmentioning
confidence: 98%
“…Although primary osteoblast to osteocyte cell transition has recently been reported in 3D by a few research groups, our model differs in the close recapitulation of complex in vivo conditions and in the self-structuring process as opposed to a preformed organic-inorganic matrix template (e.g., collagen scaffold with embedded HA particles). [45,54,55] As such, our constructs survive over much greater periods of time (i.e., 12 months compared to a few weeks); as well as developing over a real tissue length scale. We have carried out a pilot study over 3 weeks in culture to test novel compounds that can inhibit the ossification process, obtaining promising results.…”
Section: Cellular Development In Constructsmentioning
confidence: 99%